SUMO-1 conjugation to topoisomerase I: A possible repair response to topoisomerase-mediated DNA damage - Mao, Yong (The National Academy of Sciences, 2000)
Ubiquitin/26S proteasome-dependent degradation of topoisomerase I (TOP1) has been suggested to be a unique repair response to TOP1-mediated DNA damage. In the current study, we show that treatment of mammalian cells or yeast cells expressing human DNA TOP1 with camptothecin (CPT) induces covalent modification of the TOP1 by SUMO-1/Smt3p, a ubiquitin-like protein. This conclusion is based on the following observations: (i) Mammalian DNA TOP1 conjugates induced by CPT were cross-reactive with SUMO-1/Smt3p-specific antibodies both in yeast expressing human DNA TOP1 as well as mammalian cells. (ii) The formation of TOP1 conjugates was shown to be dependent on UBC9, the E2 enzyme for SUMO-1/Smt3p. (iii) TOP1 physically interacts with UBC9. (iv) Ubc9 mutant yeast cells expressing human DNA TOP1 was hypersensitive to CPT, suggesting that UBC9/SUMO-1 may be involved in the repair of TOP1-mediated DNA damage.